A Wicked Problem? Whistleblowing in Healthcare Organisations; Comment on "Cultures of Silence And Cultures of Voice: The Role of Whistleblowing in Healthcare Organisations" - Paula Hyde (Kerman University of Medical Sciences, 2016)
Mannion and Davies' article recognises whistleblowing as an important means of identifying quality and safety issues in healthcare organisations. While 'voice' is a useful lens through which to examine whistleblowing, it also obscures a shifting pattern of uncertain 'truths.' By contextualising cultures which support or impede whislteblowing at an organisational level, two issues are overlooked; the power of wider institutional interests to silence those who might raise the alarm and changing ideas about what constitutes adequate care. A broader contextualisation of whistleblowing might illuminate further facets of this multi-dimensional problem.